Examining the Role of L-Type Amino Acid Transporter 1 (SLC7A5) in Myoblasts - Akohene-Mensah, Paul (Université d'Ottawa / University of Ottawa, 2020)
Skeletal muscles represent the largest tissue mass within the body and are primarily involved in the generation of force for voluntary movement. Skeletal muscles have a remarkable capacity to repair, due primarily to the actions of muscle stem cells (MuSCs). MuSCs are normally quiescent in adult skeletal muscle; however, in response to myotrauma (trauma to muscle tissue) from muscle injury or exercise, MuSCs become activated, either undergo self-renewal to replenish the quiescent population or commit to the myogenic lineage as myoblasts, proliferate, and differentiate into myotubes in vitro or fuse to existing myofibers in vivo. This process of generating new myofibers from quiescent MuSCs is termed myogenesis and a full understanding of how myogenesis is regulated remains to be understood. Mounting evidence suggests that amino acids, particularly the essential amino acid leucine, play a role in MuSC regulation. Leucine is specifically translocated and sensed by the L-type amino acid transporter 1 (LAT1); which facilitates leucine uptake in mature myofibers. Inside the cell, leucine activates mammalian or mechanistic target of rapamycin complex 1 (mTORC1) to stimulate cell growth, proliferation, and protein synthesis. Whether leucine has direct effects on myoblast function via LAT1 is unknown. Thus, our overall objective was to begin to characterize the role of LAT1 in myogenesis. Our results indicate that myoblasts differentially expressed LAT1 throughout myogenesis with peak protein content occurring during differentiation (p<0.05 vs. early proliferation). Further, our results indicate thatpharmacological LAT1 inhibition reduced myoblast expansion and differentiation in vitro (both p<0.05 vs. control). Interestingly, myoblast LAT1 protein content did not change in response to leucine supplementation in vitro; however, was lower under in vitro atrophic conditions (p<0.05 vs. control). Based on these findings, we conclude that LAT1 plays an important role in regulating myogenesis. As such, we uncover a novel role for LAT1 in regulating muscle mass via contributing to the control of MuSC function.
Keywords: LAT1; Myoblasts